FoxP expression identifies a Kenyon cell subtype in the honeybee mushroom bodies linking them to fruit fly αβc neurons. (6th November 2017) - Schatton, Adriana; Scharff, Constance
Abstract: The arthropod mushroom bodies (MB) are a higher order sensory integration centre. In insects, they play a central role in associative olfactory learning and memory. In Drosophila melanogaster (Dm), the highly ordered connectivity of heterogeneous MB neuron populations has been mapped using sophisticated molecular genetic and anatomical techniques. The MB‐core subpopulation was recently shown to express the transcription factor FoxP with relevance for decision‐making. Here, we report the development and adult distribution of a FoxP‐expressing neuron population in the MB of honeybees (Apis mellifera, Am) using in situ hybridisation and a custom‐made antiserum. We found the same expression pattern in adult bumblebees ( Bombus terrestris, Bt ). We also designed a new Dm transgenic line that reports FoxP transcriptional activity in the MB‐core region, clarifying previously conflicting data of two other reporter lines. Considering developmental, anatomical and molecular similarities, our data are consistent with the concept of deep homology of FoxP expression in neuron populations coding reinforcement‐based learning and habit formation. Abstract : Insect FoxP, the gene homologous to vertebrate FoxP1, FoxP2, FoxP3 and FoxP4, is expressed in a mushroom body Kenyon cell subpopulation in hymenoptera and diptera. This finding is consistent with a common evolutionary origin of these particular neurones which have been shown to play a role in decision‐making and long‐term memory formation in drosophila. Similar roles of the homologous genes ('deep‐homology') across bilateria are discussed with regards to sensory stimuli evaluation and habit formation.